Amiodarone - induced skin pigmentation - Marko, Pij B. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
In last year a few cases of blue-gray skin pigmentation in photo exposed areas (face and hands) were observed at our department. Because of a chronic myocardiopathy and arrhythmia, all these patients had taken amiodarone 200 mg daily over more than two years. Histopathologic examination revealed upper and mid-dermal deposits of a yellow-black granular pigment distributed perivascularly in the cytoplasm of dermal macrophages. Special staining demonstrated that this pigment has the characteristics of lipofuscin. The small number of cases reported are probably due to the fact that this side effect of amiodarone is not so rare but frequently unrecognized.
Keywords: Amiodarone; Skin pigmentation